Attempt of basin-scale sediment quality standard establishment for heavy metals in coastal rivers. (April 2020) - Liu, Qunqun; Sheng, Yanqing; Jiang, Ming; Zhao, Guoqiang; Li, Changyu
Abstract: Heavy metal sediment quality standards (SQSs) derived from sediment quality guidelines (SQGs) are crucial in risk evaluation and environmental management. However, the establishment of SQSs is quite complex, especially for heavy metals. This study attempted to establish basin-scale SQSs for Cd, Cu, Pb and Zn based on SQGs combined with water quality standards in two coastal rivers in North China, named Jiaolai River (JL) and Jiahe River (JR), respectively. The spatial distribution, fraction, partition coefficients and environmental risk of heavy metals in sediments-porewater were investigated. The results showed that most heavy metals in sediments in JH were higher than those in JL, however, in the porewater, it exhibited an opposite trend. The geochemical fraction showed that most heavy metals in sediments were dominated by residual fraction. The partition of heavy metals between sediment and porewater were mainly affected by both sediment and porewater properties, and exogenous input of heavy metals. Contamination factors showed that Cd in sediment posed high pollution degree; the interstitial water criteria toxicity units and Nemerow Indexes suggested that heavy metal toxicities in porewater were low. The basin-scale heavy metal SQGs were calculated based on porewater quality derived from surface water quality standards using the modified equilibrium partitioning approach. The basin-scale heavy metal SQGs was classified with different grades to deduce the SQSs. Evaluated results of heavy metals in sediments based on SQSs showed lower potential bio-toxic effects in two rivers. In total, basin-scale SQGs for heavy metals were feasible for basin-scale SQSs establishment in coastal rivers. Graphical abstract: Image 1 Highlights: Standards of marine sediment and soil quality were inapplicable to river sediments. Basin-scale heavy metal SQSs could be used in river sediment management. Metal partition between sediment and porewater was affected by outer input. Evaluated results confirmed basin-scale heavy metal SQSs were feasible.